2005
DOI: 10.1016/j.asw.2005.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Differences in written discourse in independent and integrated prototype tasks for next generation TOEFL

Abstract: We assessed whether and how the discourse written for prototype integrated tasks (involving writing in response to print or audio source texts) field tested for Next Generation TOEFL® differs from the discourse written for independent essays (i.e., the TOEFL Essay®). We selected 216 compositions written for 6 tasks by 36 examinees in a field test-representing score levels 3, 4, and 5 on the TOEFL Essay-then coded the texts for lexical and syntactic complexity, grammatical accuracy, argument structure, orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
199
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(212 citation statements)
references
References 47 publications
8
199
1
4
Order By: Relevance
“…However, these studies did not analyze integrated-writing tasks, but instead used independent writing tasks such as free writing and narratives. Although integrated-writing assessment studies have demonstrated that lexical features differentiate essays at rating levels (Cumming et al, 2005), other research studies have reported no difference in lexical diversity features based on essay rating (Gebril & Plakans, 2013). Furthermore, studies of prompt characteristics have shown that prompt variation in terms of the difficulty of source texts impacts the text ratings (Cho et al, 2013).…”
Section: La Présente éTude a Comparé Des Rédactions éCrites Par Desmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these studies did not analyze integrated-writing tasks, but instead used independent writing tasks such as free writing and narratives. Although integrated-writing assessment studies have demonstrated that lexical features differentiate essays at rating levels (Cumming et al, 2005), other research studies have reported no difference in lexical diversity features based on essay rating (Gebril & Plakans, 2013). Furthermore, studies of prompt characteristics have shown that prompt variation in terms of the difficulty of source texts impacts the text ratings (Cho et al, 2013).…”
Section: La Présente éTude a Comparé Des Rédactions éCrites Par Desmentioning
confidence: 99%
“…Similarly, researchers have shown that lower proficiency L2 writers may struggle to understand the source materials provided for integrated-writing exams and may not be able to select the appropriate or relevant information to use in their essays, ultimately affecting the overall quality of their texts (Gebril & Plakans, 2013;Sawaki, Quinlan, & Lee, 2013;Wolfersberger, 2013). Whereas some integrated-writing research has shown a positive relationship between lexical sophistication (type/token ratio) and text ratings (Cumming et al, 2005), other studies have found that average word length (another measure of lexical sophistication) was not associated with essay ratings (Gebril & Plakans, 2013;Sawaki et al, 2013). VOLUmE 32, iSSUE 2, 2015…”
Section: La Présente éTude a Comparé Des Rédactions éCrites Par Desmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, different measures of lexical competence have been repeatedly proved to correlate with overall writing quality (e.g., Cumming, Kantor, Baba, Erdosy, Eouanzoui, & James, 2005;Laufer & Nation, 1995). In this study; a three-dimensional model would be used to determine the lexical competence of the participants and to examine the potential of this model to account for the participants' writing proficiency.…”
Section: Second Language Writing Performancementioning
confidence: 99%
“…Despite the consensus that vocabulary affects the quality of writing strongly (Cumming, Kantor, Baba, Erdosy, Eouanzoui, & James, 2005;Munice, 2002), more empirical evidence is required to indicate the possible relationship between vocabulary knowledge and writing quality (Lee, 2003).…”
Section: Introductionmentioning
confidence: 99%